(untitled) (SAARC Journal of Agriculture, 2018)
Thirty jhum rice genotypes of hilly origin were studied for genetic variability, correlation and path analysis under medium high land of Bangladesh Rice Research Institute, Gazipur, Bangladesh. The experiment was laid out in a Randomized Complete Block Design (RCBD) with three replications for the period of March to July (Aus season), 2016. Analysis of variance revealed significant difference among the genotypes for all the characters studied. The PCV values were greater than GCV, revealing little influence of environment in character expression. High values of heritability along with high genetic advance were observed for filled grain and plant height. Such outcomes suggested predominance of additive gene action in gene expression for these characters. Grain yield showed positive association with number of effective tiller and thousand grain weight at genotypic in conjunction with phenotypic level. Most of the traits had significant genetic variability besides, plant height and panicle length exhibited positive direct effect together with positive correlation with yield. Thousand grain weight possessed negative direct effect but highest positive significant correlation with yield. SAARC J. Agri., 16(1): 193-203 (2018)